2001
DOI: 10.1177/026565900101700201
|View full text |Cite
|
Sign up to set email alerts
|

Why ask questions? Contextual effects on grammatical structure in the language production of children with specific language impairment

Abstract: In this small-scale study we investigated the influence of different aspects of context on the language production of children with specific language impairment (SLI). Each of the variables, type of partner, the partner’s interactional style and the type of material used for eliciting conversation, was related to the probability of the use of a set of grammatical constructions by the child. The results show that the interactional style of the conversational partner as well as the type of elicitation material u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…On the other hand, the SLPs asked as many questions in conversation and training. Nettelbladt, Hansson and Nilholm (2001) found that grammatical complexity was higher in productions that followed a non-soliciting turn from the SLP and suggested that a highly soliciting style may restrict the child's language production. Instead, our results indicate that linking to the child's focus is more crucial than whether the interaction style is soliciting or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the SLPs asked as many questions in conversation and training. Nettelbladt, Hansson and Nilholm (2001) found that grammatical complexity was higher in productions that followed a non-soliciting turn from the SLP and suggested that a highly soliciting style may restrict the child's language production. Instead, our results indicate that linking to the child's focus is more crucial than whether the interaction style is soliciting or not.…”
Section: Discussionmentioning
confidence: 99%
“…Language intervention has not been extensively explored in Sweden, with some exceptions. One is the study by Nettelbladt, Hansson and Nilholm (2001) in which the interactional style of professional and non-professional conversational partners was explored. They found that the grammatical complexity of children with SLI was higher in productions that followed a non-soliciting turn from the SLP than in those that followed a soliciting turn.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of assessment tools available in many of the L1s spoken among North American children and the impracticality (and methodological concerns) of translating English tests, many researchers have argued for alternate means of language assessment for bilingual children. Among such alternatives, discourse analysis (Craig & Evans, 1992 ; Nettelbladt, Hannson, & Niholm, 2001 ; Thompson, Craig, & Washington, 2004 ) and parent interview (Paradis et al, 2010 ) have been suggested as more accurate, or ecologically valid, measures of language proficiency than standardized tests.…”
mentioning
confidence: 99%
“…In Swedish studies of talk-in-interaction in children with language impairment the Initiative-Response analysis (Linell et al, 1988) has been used (Hansson et al, 2000;Nettebladt and Hansson, 1993;Nettelbladt et al, 2001). This is a method for analysing spoken dialogues, designed to capture the dynamics, the coherence and the dominance conditions within a dialogue.…”
Section: Perceptual Evaluationsmentioning
confidence: 99%